Approximation in Quantum Quadrupole at Juergen Model for Nuclear Reactor Control Rod Blade Based on ce {Th_xDUO2} Nano Materials - Hardiyanto, Moh. (Omega: Jurnal Fisika dan Pendidikan Fisika, 2018)
The functional of a multi purpose research nuclear reactor control rod blade nuclear reactor is stabilized and controlling devices for nuclear chain reactions, the existing of Cerenkovs radiation impact and thermal neutron flux in reactor chamber. This research was conducted in Large Hadron Collider (LHC) - Muon Hadron Division at CERN, Lyon - France under International Research between Canadian Deuterium Uranium (CANDU) - Nuclear Reactor and Betha Group Section for sub-particles for nanomaterial. Using Juergen Model with quantum states approaching and testing by Muon-Hadron Stirrer equipment had determined the ce {Th_xDUO2} derivatives materials. This material shown the strength of thermal neutron flux absorbed about 2.56 Ã 10âµ â 1.94 Ã 10â¶ Ci/mm, the value of Electrical Conductivity is 26.62 â 29.98 in 800Â° - 890Â° C temperature, however at 2.1 Ã 10âµ Ci/mm thermal neutron flux condition is 29.44 â 37.88 in IAEA standard. At 450 tesla magnetic field and 2.1 Ã 10âµ Ci/mm thermal neutron absorber, the crystalline structure reduction is 6.88% until 10.95% for 25 years period in 45.7 megawatts with ce UO2 more enrichment and ce Pu2O also ce {Th2O_y} nuclear fuel element matrix.